Allele frequencies ofSTRs (CSFIPO, TPOX and THOI) in random Than population of Eastern Malaysia - Tiong, Kadi (Universiti Sains Malaysia, 2006)
Advances in DNA technology and the discovery of DNA polymorphisms have led to creation of DNA databases using the microsatellites or short tandem repeat (S1Rs). The main purpose of creating the DNA database is to study the polymorphism of DNA segments among individuals within the same population and among different human populations. Individuals may have ditJerent combinations of the variants and populations will have different frequencies of those variants. These levels of variation in DNA sequence are useful in human identification purpose. In the present study, the distribution of allele frequencies for three validated S1Rs- CSFIPO, TPOX and THOJ was compiled for the ethnic Iban population of Eastern Malaysia. DNA samples from 100 random Iban individuals were processed using multiplex primer kit. The distributions of allele frequencies of Iban population are unique.